PHOTOPHYSICAL PROPERTIES OF PERYLENE MOLECULE - ŢIMBOLMAŞ, Larisa Milena; CHIŞ, V. (Studia Universitatis Babeș-Bolyai Physica, 2017)
In this work we investigated computationally the photophysics of the perylene molecule using the time‐dependent Density Functional Theory (TD-DFT). Particularly, we were interested in the vertical emission energy and radiative fluorescence lifetime of the investigated molecule. Using adequate models and proper computational methodologies we were able to satisfactorily predict the experimentally reported photophysical properties of the perylene core.